(untitled) (Bangladesh Critical Care Journal, 2026)
Background: Acute respiratory distress syndrome (ARDS) continues to pose major prognostic challenges, with high mortality rates and traditional oxygenation indices limited by their reliance on invasive arterial blood gas measurements. Growing evidence supporting noninvasive markers such as the ratio of oxygen saturation in pulse oximetry and fraction of inspired oxygen (SpO₂/FiO₂) and oxygen saturation index (OSI) prompted this study to explore OSI as a safer, practical predictor of clinical outcomes in critically ill ARDS patients. Methods: This prospective observational study enrolled 150 adult ARDS patients at Dhaka Medical College Hospital, following strict Berlin diagnostic criteria and PEEP-supported ventilation. After obtaining ethical approval and informed consent, detailed demographic, clinical, and comorbidity data were collected at admission. Daily monitoring during the first four ICU days included hemodynamics, ventilator settings, ABG analysis, and calculation of APACHE II, Oxygenation Index (OI) and Oxygenation Saturation Index (OSI) values. Key outcomes, ventilation duration, length of ICU stay, multiorgan failure, and hospital mortality, were recorded to evaluate the predictive performance of oxygenation indices. Result: Most of the study population were in older age groups, with males comprising 64% and occupations spanning service, business, day labour, and household roles. Hypertension (48%), smoking (40%), diabetes (32%), and obesity (20%) were the major risk factors, while severe traumatic injury (48%) and sepsis-related causes dominated the etiological profile. In-hospital mortality was 36%, and patients experienced prolonged ventilation, ICU stay, and hospitalization. Multiple variables, including age (p<0.001), APACHE II score (p<0.001), oxygenation indices (OI p=0.001; OSI p<0.001), MAP (p=0.001), and oxygenation ratios (SpO2/FiO2 p=0.009; PaO2/FiO2 p=0.015), were significantly associated with ICU mortality. OSI demonstrated strong positive correlations with OI, APACHE II score, ventilation duration, and ICU stay, while SpO2/FiO2 closely correlated with PaO2/FiO2. In ROC analysis, OSI (AUC 0.645, p=0.003) and OI (AUC 0.641, p=0.004) outperformed traditional oxygenation ratios, while APACHE II (AUC 0.847, p<0.001) remained the strongest predictor of hospital mortality. Conclusion: This study demonstrates that OSI closely mirrors illness severity and reliably predicts mortality in ARDS, performing on par with or better than conventional oxygenation indices. Its strong correlations and noninvasive nature position OSI as a practical bedside tool for early risk stratification, especially in settings where frequent arterial blood gas analysis is challenging. Bangladesh Crit Care J March 2026; 14 (1): 39-44